Sections of Hungarian Contemporary Architecture and Fine Arts - Harangi, Attila; Török, Dávid (International Journal of Engineering and Management Sciences, 2016)
In my study I have examined the sections of Hungarian contemporary architecture and fine arts. In the historical overview it has become clear that two turning points have influenced contemporary arts: the total art work (Gesamtkunstwerk) of the Ghotic and Baroque styles. I listed the sections in three categories: metamorphosis, relationship and section. The sections are the highest level of these categories. I explained my research in detail by analyzing these sections, at János Megyik’s art and his Gate statue at Life Science building and library at the University of Debrecen.